Understanding SEL to Create a Sense of Belonging: The Role Teachers Play in Addressing Students' Social and Emotional Well-Being - Blanca N. Ibarra (Arizona State University, 2022)
This inquiry examines the benefits of utilizing social-emotional learning in today's classrooms to address students' academic and social-emotional needs. Now, more than ever, as teachers have transitioned from remote instruction to face-to-face or blended learning, particular emphasis must be placed on addressing students' social and emotional needs (Fagell, 2021) while addressing learning loss. Social-emotional learning (SEL) may have been in place in school systems before the COVID-19 pandemic; however, understanding SEL and the instructional practices that contribute to developing a learning environment that nourishes students' sense of belonging is necessary to inform teacher pedagogical practices post-pandemic. Teachers play a critical role in establishing a learning environment suitable for nurturing students' sense of belonging (Jennings & Greenberg, 2009). As teachers attempt to provide a sense of normalcy in the classroom, they must skillfully balance designing instruction, creating an inviting classroom community, and helping students "feel" safe and supported.